Reading-in-the-Small: a study of reading on small form factor devices - Marshall, Cathy; Ruotolo, Christine (Proceedings of the 2nd ACM/IEEE-CS Joint Conference on Digital Libraries (JCDL '02), 2002)
The growing ubiquity of small form factor devices such as Palm Pilots and Pocket PCs, coupled with widespread availability of digital library materials and users’ increasing willingness to read on the screen, raises the question of whether people can and will read digital library materials on handhelds. We investigated this question by performing a field study based on a university library’s technology deployment: two classes were conducted using materials that were available in e-book format on Pocket PCs in addition to other electronic and paper formats. The handheld devices, the course materials, and technical support were all provided to students in the courses to use as they saw fit. We found that the handhelds were a good platform for reading secondary materials, excerpts, and shorter readings; they were used in a variety of circumstances where portability is important, including collaborative situations such as the classroom. We also discuss the effectiveness of annotation, search, and navigation functionality on the small form factor devices. We conclude by defining a set of focal areas and issues for digital library efforts designed for access by handheld computers.